803 Sleep Disturbances in Patients with Frontotemporal Dementia. (3rd May 2021) - Walker, Nathan; Vaughn, Bradley
Abstract: Introduction: Frontotemporal dementia (FTD) is a degenerative process and, as the name implies, involves the frontal and temporal lobes of the brain. Patients with FTD make up 10–15% of all cases of dementia and 20% diagnosed before age 65, however not much is reported about sleep disturbances in these patients. Given the area of neuronal loss one would expect that sleep may be influenced early and by issues in arousal mechanisms and in breathing pattern. This study examined the polysomnography (PSG) reports of patients with a diagnosis FTD. Methods: A retrospective chart review was performed to identify patients with both a diagnosis of FTD and having undergone a PSG. 23 patients were identified as fulfilling both requirements. Data recorded included, diagnosis, age at time of PSG, Epworth sleepiness scale (ESS), total sleep time (TST), wake after sleep onset (WASO), sleep latency (SL), REM sleep latency, sleep efficiency (SE), percentage of stage N1, N2, N3, and REM sleep, apnea-hypopnea index (AHI), presence of Cheyne-Stoke breathing, periodic limb movement index, and presence of REM without atonia. Results: Patient age ranged from 57–85 years. Average ESS was 8.8 with only 5 patients reported excessive daytime sleepiness(as assessed by ESS). The average TST was 290 minutes, average SL was 37.9 minutes, average WASO was 147.5 minutes, and average sleep efficiency was 60.3%. Patients spent the majority of time in N2 sleep with an average of 68.3% of the time spent in N2. The average time spent in N3 was 9.6% of sleep. 8.9% of sleep was spent in REM. 83% of patients were diagnosed with sleep apnea (as defined by an AHI > 5), with an average AHI of 20.2 events/hour. Cheyne-Stokes breathing was only noted in 4 of the 23 patients, or 17%. Periodic limb movements of sleep were noted in 48% of the patients (n=11). REM without atonia or RBD was not noted for any patients. Conclusion: This study shows that patients with FTD suffer from typical sleep disturbances, however there is a high prevalence of sleep apnea as well as PLMS. In addition, patients with FTD have decreased sleep efficiency with increased WASO. Support (if any):